Pengaruh Sales Promotion Dan Harga Terhadap Keputusan Pembelian Pada Fore Coffee Jatimulya Bekasi - Lita Oktarina; Murti Wijayanti; Dody Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this research is to find out whether Sales Promotion and Price influence Purchasing Decisions at Fore Coffee Jatimulya Bekasi. This type of research is quantitative and the data analysis used is the classic assumption test and multiple linear regression analysis, to test and prove the research hypothesis using SPSS version 27 application. There were 110 respondents in this research population. Bhayangkara University, Jakarta Raya is the subject of this research. The results of the research show that partially Sales Promotion has a significant and positive influence on purchasing decisions, with tcount of 2.609 > t table 1.982, significant level of 0.010 <0.05. Partially, price has a significant and positive effect on purchasing decisions with tcount of 5.676 > t table 1.982, significant level of 0.000 <0.05. Sales promotion and price simultaneously influence purchasing decisions as seen from fcount 36,598 f table 3.08 where 0.000 0.05 is a significant value.